Analysis of the Mediating Role of Self-Efficacy and Self-Esteem on the Effect of Workload on Burnout’s Influence on Nurses’ Plans to Work Longer - Molero, María del Mar; Pérez-Fuentes, María del Carmen; Gázquez, José Jesús (Frontiers in Psychology, 2018)
At the present time, we know that there is a positive relationship between self-efficacy and self-esteem in which positive beliefs about one’s own efficacy increase one’s sense of self-worth as stressful situations of a heavy workload are coped with successfully, and this, in turn, affects the nurses' plans to work longer. Analyze the mediating role of self-efficacy and self-esteem in the effect of workload, measured as the number of users attended to during a workday, on burnout in nursing professionals. A sample of 1307 nurses aged 22 to 60 years who were administered the Brief Burnout Questionnaire, the General Self-Efficacy Scale and the Rosenberg Self-Esteem Scale, and workload, measured as the number of users attended to during the workday. The results show that professionals with high levels of self-efficacy also scored higher on global self-esteem. Burnout correlated negatively with both variables (Self-efficacy and Self-esteem). Three clusters were found with the variables (Self-efficacy, Self-esteem and Workload) showing significant differences in burnout scores among clusters. Self-efficacy and self-esteem function as buffers of the negative effects of workload on burnout. Organizations should design interventions for promoting the personal resources of their workers through training activities and organizational resources (e.g., redesigning job positions) to promote satisfaction and wellbeing of employees, making their stay at work greater.